Health values of cassava compared to wheat and yam in relation to diabetes and dyslipidaemia management - Onodu, Bonaventure; Culas, Richard; Nwose, Ezekiel U. (International Journal Of Community Medicine And Public Health, 2020)
The objective of the study was to evaluate how diabetes and dyslipidaemia can be managed by increasing the consumption of root and tuber crops such as cassava and yam. Journal literatures based on research reports as well as institutional publications and databases on nutritional values of various foods were reviewed. Critical reviews were also performed to synthesize a comparison between the various foods, especially in terms of their fibre values. The critical review shows that guidelines devoted six pages to protein-energy malnutrition and another seven pages on micronutrients. However, there is no mention of the dietary fibre values of the staple root and tuber food crops. From the narrative review, previous report showed that carbohydrate or fibre and fat or fibre ratios are negligible in the raw products, but highest in wheat flour and higher in yam relative to cassava flour. A further comparative review in terms of proximate analysis of the foods elaborates that unprocessed wheat is high in crude protein, carbohydrate and fibre. Thus, the extent or nature of processing is a key factor. Whether wheat has better health value over root and tuber crops has neither being expatiated, nor cassava and yam acknowledged as having any medical value relative to wheat. Since fat is pro-obesity and pro-diabetic while fibre is anti-dyslipidaemic; the foods based on processed wheat flour may possess the least pharmacological values relative to the indigenous carbohydrate food crops. This report provides indication of medical nutrition therapy potentials of indigenous carbohydrate food crops in Delta state of Nigeria.